Implicações do gene TP53 e do vírus do papiloma humano no câncer de próstata - Saraiva, Ana Cândida Machado (2002)
The prostate gland can be assaulted by many pathologies. Among them the prostate câncer is the 2nd death cause on men older than 50 years old. Although the etiology of this disease is not well comprehended, the genetic alterations and the presence of infectious agents have been suggested as associated to the development of this câncer. One of the most frequent genetic alterations on the cancers are the ones related to the tumor suppressor gene TP53, responsible for the cell cycle control and apoptosys. In the beginning of the 90s, many works also arose on the attempt to establish a relationship between the human papilloma virus (HPV) infection and the prostate câncer. Within this context, this work had as objectives, to evaluate the HPV prevalence, to analyze the Arg72 Pro polymorphism, to associate this polymorphism to the HPV presence and to track for mutations on the exons 5 to 8 of the PT53 gene in patients presenting prostate câncer. 36 prostatic tissues were analyzed, seeing that these proceeding were from adenocarcinomas, BPH and PIN and peripheral blood of some of these patients, as well as of a group of men randomly chosen on the population. The techniques used for the HPV detection and typing were the PCR and nested PCR. For the Arg72Pro polymorphism analysis and for the tracking of mutations, the PCR and LIS-SSCP techniques were used. There were no differences on the frequencies of the Arg72Pro polymorphism between the BPH and PCa tissues (p=0,36; 95% reliance interval). The frequencies obtained on the blood of some patients with prostatic pathologies also did not differed significantly, whereas the BPH group did not differ from the PCa group (p=0,72,xviii 95% reliance interval), nor this from the frequency found on the population (p=0,08, 95% reliance interval). It was detected Loss of Heterozigosity (LOH) in 9 (34,61%) patients that lost the Pro allele, becoming Arg/Arg. Among these individuais, 5 (35,71%) belonged to the câncer group, 3 (37,5%) to the BPHs and 1 (25%) to the PINs. Among the 36 analyzed patients for the HPV infection, by means of PCR and nested PCR, only 2 (5,55%) presented positivity for HPV types 16 and 39. The t Test, showed that there were no significant differences for the HPV presence among the samples obtained by TUR and radical prostatectomy, nor among the malignant and benignant analyzed tissues. The positive patients for the HPV infection presented an homozygous genotype for arginine, however, the low prevalence of this infection did not allow an association to the Arg 72Pro polymorphism. A possible mutation was detected on the exon 6 in one patient with prostate câncer. In this manner, the low prevalence of the HPV infection, and the non-association of this with the Arg72Pro polymorphism as well as the rare frequency of mutatíons on the analyzed exons suggest that these would not be the essential mechanisms for the prostate câncer development. However, the LOH event could be associated to the progression or development of this tumor, being a precocious or intermediate event, yet not obligatory. More detailed and amplified studies should be done to clear these results, searching for directions to better comprehend the physiological procedures, which result on the genotype-environment association, on this affection.